Правове положення договору емфітевзису за українським законодавством - Фролова, Н. В.; Frolova, N. (Одеса : Юрид. л-ра, 2014)
Contractual relations in the use of land for agricultural purposes to spread in our time. Develop contractual relations in land law, which is why the issue of rights to other people’s land in need of improvement and development. The article is devoted to the contract of land use for agricultural purposes (perpetual lease), an analysis of its essential conditions and problems of improvement of legislation in this area.
Фролова Н. В. Правове положення договору емфітевзису за українським законодавством / Н. В. Фролова // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 223-227.
Keywords: емфітевзис; земельне право; земельно-правові договори; эмфитевзис; земельное право; земельно-правовые договоры; emphyteusis; land law; land law contracts